2020
DOI: 10.1088/1755-1315/453/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of the Sugarcane Leaves Cutting Process of the Electric Returning Machine

Abstract: In order to improve the sugarcane leaves cutting effect of electric sugarcane leaves returning machine, the sugarcane cutting process is modelled and simulated by ANSYS/LSDYNA software. It shown that in the double-support cutting mode, the cutter roller ensures the multi-layer sugarcane leaves were cut at the rotate speed of 800 rpm. During the cutting process of sugarcane leaves, the stress is mainly concentrated at the incision, and the sugarcane leaves on the side of the blade are subjected to greater stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Thus, we designed four slopes (5°, 10°, 15° and 20°) in this study. Moreover, sugarcane leaves and stalks were produced at a ratio of 1:5 (Lin et al, 2020). Field investigations have shown that the sugarcane yield ranges from 1 to 7 t/ha, which suggests that the sugarcane leaf yield ranges from 2.5–17.5 t/ha.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we designed four slopes (5°, 10°, 15° and 20°) in this study. Moreover, sugarcane leaves and stalks were produced at a ratio of 1:5 (Lin et al, 2020). Field investigations have shown that the sugarcane yield ranges from 1 to 7 t/ha, which suggests that the sugarcane leaf yield ranges from 2.5–17.5 t/ha.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated that years of soil and water conservation measures in lateritic red soil areas have achieved far fewer benefits than losses caused by soil erosion (Liu & Han, 2021). Drawing on the experience in other regions, returning sugarcane leaves to the field may be the best approach to improve the soil quality in lateritic red soil areas and address the existing atmospheric pollution caused by large‐scale incineration (Lin et al, 2020). The effect of returning sugarcane leaves to the field on the soil quality, disease incidence, pests and weeds in agriculture, sugarcane output and greenhouse gas emissions in soil has been extensively studied by many scholars (Hilton et al, 2017; Li et al, 2019; Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation